In Vitro, In Vivo Antiasthmatic Studies of Talinum portulacifolium F. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This investigation has been conducted to evaluate the antiasthmatic activity and phytochemical characterization using gas chromatography-mass spectrum (GC-MS) analysis of the leaf extracts of Talinum portulacifolium. Materials and Methods: Hydroalcoholic and acetone extracts of the plant were prepared. Preliminary phytochemical screening has been conducted. Antiasthmatic activity was determined by two experimental models. In vivo methods, histamine and acetylcholine (Ach)-induced bronchospasm in guinea pigs were studied. Pre convulsion time (PCT) was calculated. In vitro, experimental methods such as histamine and Ach-induced contractions in ileum were also studied. Percentage inhibition of contractions was calculated. Phytochemical characterization was studied using GC-MS analysis. Results and Discussion: In histamine and Ach-induced bronchospasm studies acetone extracts of the plant have significantly increased PCT 10.69 and 10.52 (**P < 0.01), one-way analysis of variance (ANOVA) Tukey’s test compared with control. Histamine and Ach-induced ileum contraction studies also showed that the acetone extracts exhibited response 2.6 with 47% and 2.2 with 40% inhibition (*P < 0.05). The results were expressed by one-way ANOVA, Dunnett’s test. The results of GC-MS analysis depicted following phytoconstituents with major peak area, namely, 79.29% methoxy-bis (cyclopentadiene), 2.83% - 5,10-dihexyl-5,10-dihydroindolo[3,2-b]indole-2,7-dicarbaldehyde, and 1.84% - 1,2-bis[3,4-dimethoxy benzyl]-1,2-bis (methoxymethyl) ethane. Conclusion: The results of this study clearly indicate that the hydroalcoholic and acetone extracts of T. portulacifolium can be used as promising antiasthmatic agents. The activity may be due to the presence of phytochemicals reported through GC-MS.